Research on the Application of BIM Technology in Architectural Education and the Development of an Informatized Teaching Model - Yu, Hongfei (Research and Advances in Education, 2025)
This study investigates the application of Building Information Modeling (BIM) technology in architectural education and explores its transformative impact on traditional teaching models. Through a comprehensive review of the literature and analysis of case studies, this research delves into how BIM technology, with its characteristics of visualization, parametric design, and collaboration, enhances the interactivity and practicality of architectural education. It provides students with a more intuitive and dynamic learning environment. The study proposes a framework for an informatized teaching model in architectural education based on BIM technology, detailing the construction approach, implementation strategies, and practical application effects. It also addresses potential challenges such as technical barriers, teacher training, and cost investment, offering corresponding solutions. The results indicate that the application of BIM technology significantly improves the quality and efficiency of architectural education, providing new ideas and methods for the informatization of architectural education with important theoretical and practical significance.